Feasibility of training group exercise class instructors to adopt a motivationally adaptive communication style - Hancox, Jennie; Thogersen-Ntoumani, Cecilie; Quested, Eleanor; Ntoumanis, Nikos (Edizioni Luigi Pozzi s.r.l., 2018)
This study examined the feasibility of a 10-week self-determination theory-based training programme delivered to 24 group exercise instructors. Feasibility of implementing the programme was explored in terms of (1) recruitment, (2) rates of adherence and retention, and (3) acceptability. Results revealed modest uptake (51%) and excellent workshop attendance (either in-person or online) and retention rates (96%). Coding of the interview data revealed 9 main themes with regard to the acceptability of the training programme: satisfaction with content, challenging current motivational practices, perceived relevance of the motivational strategies, social support, mix of theory and practice, usefulness of learning resources, need-supportive delivery, multi-stage structure, and value for professional development. The findings can inform the development, design, and implementation of future research with the target population.